2016
DOI: 10.1086/684412
|View full text |Cite
|
Sign up to set email alerts
|

Hidden in Plain Sight: How Ventral Line Markings in Chameleons May Enhance Camouflage

Abstract: Chameleons, lizards often synonymous with camouflage for their color-changing abilities, possess a variety of permanent coloration patterns whose evolutionary significance remains largely unknown. In this study, we explore the potential for white ventral line markings in species across the genus Chamaeleonidae to function as a camouflage pattern against diurnal predators. Diurnal behavioral field studies of the white-lined chameleon Furcifer viridis showed that individuals typically exposed ventral line markin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Lateral displays are positively associated with fighting ability in other male chameleon species (Bradypodion pumilum; [54]). Taken together, the findings by Resetarits & Raxworthy [53] suggest that lateral lines function as a secondary sexual signal in males and may not have an antipredator function, and that arboreal habitats increase the signal efficacy of these lateral lines to conspecifics. These findings, however, contradict our own observations on the common chameleon which demonstrated that during courtship events lateral lines are not presented.…”
Section: Contextual Appearance Of Colour Patternsmentioning
confidence: 77%
See 2 more Smart Citations
“…Lateral displays are positively associated with fighting ability in other male chameleon species (Bradypodion pumilum; [54]). Taken together, the findings by Resetarits & Raxworthy [53] suggest that lateral lines function as a secondary sexual signal in males and may not have an antipredator function, and that arboreal habitats increase the signal efficacy of these lateral lines to conspecifics. These findings, however, contradict our own observations on the common chameleon which demonstrated that during courtship events lateral lines are not presented.…”
Section: Contextual Appearance Of Colour Patternsmentioning
confidence: 77%
“…A recent comparative study on many chameleon species suggests that the lateral lines serve as a secondary sexual signal [ 53 ]. In their study, Resetarits & Raxworthy [ 53 ] found a positive correlation between the presence of the ventral or lateral lines and arboreal habits. They also showed in a series of behavioural trials on Chamaeleo viridis that the lateral lines were hidden from the predator and were observed only on males.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chameleons were allowed to interact with the predator for 30 s (further durations did not elicit an additional response), with each trial being video recorded for subsequent scoring of behavioral responses. Behavioral responses were categorized as either: (i) aggression (body inflation, mouth gaping, hissing and/or lunging); (ii) fleeing (quick escape from the predator); (iii) crypsis (changing color to more closely match background); (iv) ring-flipping (rotating to the side of the branch opposite from the predator's view; Resetarits and Raxworthy, 2016 ); (v) free-falling (dropping from the branch); or (vi) leaf-mimicking (slow, back-and-forth movement imitating foliage).
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…We observed that A. aquaticus on moss-speckled surfaces often bore more brightly colored stripes, whereas those on darker substrates bore inconspicuous stripe coloration (dark brown) (L. Swierk, personal observation). Adopting brown stripes may enhance substrate-matching on the dark substrates, whereas displaying bright, irregular stripes could be a form of disruptive camouflage against brightly mottled surfaces (Cuthill et al 2005;Resetarits and Raxworthy 2016); an examination of predator vision models and the light environments of these habitats might confirm this prediction. Such a link between coloration and camouflage would also complement our finding that stress is associated with brighter body coloration: green speckled surfaces tend to be much more exposed than uniformly dark crevices or walls, and thus green perches could be more stressful for A. aquaticus.…”
Section: Figmentioning
confidence: 98%